Difficult heritage : negotiating the Nazi past in Nuremberg and beyond. - Macdonald, Sharon (Taylor & Francis, 2008)
How does a city and a nation deal with a legacy of perpetrating atrocity? How are contemporary identities negotiated and shaped in the face of concrete reminders of a past that most wish they did not have? Focusing on the case of Nuremberg, this text explores these questions and their implications.